2008. Effective and Early Diagnosis of Pneumonia in Patients With Acute Leukemia in a Comprehensive Cancer Center: How Can We Improve the Microbiological Diagnosis?. (26th November 2018) - Sakurai, Aki; Bala-Hampton, Justin; Mulanovich, Victor E; Cortes, Jorge E; Adachi, Javier
Abstract: Background: Pneumonia is one of the main causes of morbi-mortality in acute leukemia (AL) patients. The positive yield of microbiology diagnosis is still significantly low. The aim of the study was to evaluate the possible impact of use of diagnostic methods (within first 48 hours of diagnosis) in AL patients with pneumonia during chemotherapy. Methods: Retrospective study (January 2017–December 2017) at MD Anderson Cancer Center. The medical records of adult patients with AML, MDS, or ALL who developed CT-confirmed pneumonia after induction or second-line chemotherapy were reviewed, including demographic, clinical, microbiology data, and outcomes. Results: During 2017, 174 patients with AL developed pneumonia confirmed by CT chest. Fifty (29%) of them during induction/second-line chemotherapy: 42 (84%) AML, five (10%) MDS, and three (6%) ALL. Thirty-one (62%) showed consolidation in CT, 14 (28%) nodules, and five (10%) both findings. Mean age was 65 (SD: 11.5, range: 24–87) years with 46% males. Thirty-three (66%) patients had neutropenia (ANC<500) at the time of pneumonia. ID was consulted in 38 (76%) and pulmonary in 37 (74%) patients. Bronchoscopy/BAL (bronch) was performed in only 24 (48%) patients, still with the highest diagnostic yield (13/24, 54%) compared with other diagnostic methods (sputum and blood cultures; and galactomannan, β-glucan, and cryptococcal antigen in serum). Twelve of 24 (50%) patients had an early bronch (within 48 hours), with higher identification of bacteria (3/12, 25%), fungi (2/12, 16.7%), and virus (3/12, 25%) compared with those 12 performed later. A trend of more viral infection (6/12, 50%), including CMV, was found in late-performed bronch (>48 hours after diagnosis). The patients with early bronch were sicker, with higher rate of ICU admission (42% vs. 0% in late group) and in-hospital mortality (25% vs. 8% in late group). However, those patients who underwent bronch later had a higher rate of 30-day re-admission (33% vs. 22% in early group). Conclusion: Bronchoscopy/BAL was the best diagnostic test in patients with AL and CT-confirmed pneumonia, even though it was only performed in 48% of patients. Early bronchoscopy (first 48 hs) has better diagnostic yield than late bronchoscopy (>48 hs), directing the antimicrobial therapy on these patients (based on the identification of bacteria, fungus or viruses), and decreasing the 30-day re-admission rate. Disclosures: J. Adachi, Merck: Grant Investigator, Research grant.